Akuntansi Forensik Sebagai Instrumen Antikorupsi dalam Pengelolaan Keuangan Daerah: Tinjauan Literatur - Suka, Thea Erin Kristy Br Ginting (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study is motivated by the high level of corruption in regional financial management, which leads to state financial losses and a decline in public trust in local governments. Forensic accounting emerges as an approach not only capable of detecting fraud but also of providing legally admissible evidence. The objective of this research is to analyze the role of forensic accounting as an anti-corruption instrument in regional government through a literature review. This study adopts a qualitative descriptive method using a literature review approach. Data were obtained from scientific journals, audit reports, policy documents, and official publications from supervisory institutions such as the Audit Board of Indonesia (BPK) and the Corruption Eradication Commission (KPK), all of which are relevant to forensic accounting and public financial management. The analysis involved a critical synthesis of empirical and theoretical findings from the reviewed literature. The study reveals that forensic accounting plays a significant role in identifying fraud patterns, supporting litigation with legal evidence, and strengthening internal control mechanisms in regional financial management. These findings are consistent with prior research showing that forensic approaches improve transparency and accountability in public sector financial governance